EXPLORING THE FEELINGS OF STUDENT VICTIMS OF BULLYING AND PERPETRATORS OF BULLYING AT MIDDLE SCHOOL - Candra Destiyanti , Ika (Universitas Efarina, 2022)
Bullying is an act of physical and psychological violence by perpetrators towards victims of bullying. The tendency of bullies is that they have had a history of violence in the past. This study uses a narrative qualitative methodology with semi-structured interviews with victims and perpetrators of bullying at school. The results of this study are that awareness of bullying as an act of violence is a strong basis for perpetrators not to bully repeatedly. Parents' occupation and income do not have a dominant impact on child violence at school because anyone can potentially become a bully or a victim of bullying at school. The conditions and situation of children at school who do not have the ability to solve problems is an important factor in them becoming perpetrators or victims of bullying. This research provides insights for observers of children and adolescents to be more concerned about their problems of bullying and for teachers to communicate a lot to students who experience bullying and bullies before deciding on punishment.